Estimating Power Outage Costs Based on a Survey of Industrial Customers. Issue 4 (20th August 2013) - Yoshida, Yoshikuni; Matsuhashi, Ryuji
Summary Thousands of factories in Japan responded to a survey on power outage costs for industrial customers. From across the country, 5139 facilities designated as energy management factories answered questions about their power consumption and the loss of production value due to a hypothetical hour‐long power outage on a summer weekday. Using their responses, we estimated the median unit cost of a power outage across all sectors to be 672 yen/kWh. The service sector of amusement and hobbies and the manufacturing sector that makes electronic information and communication equipment have relatively high unit costs for power outages. The direct cost of damage from a specified power outage across all sectors totaled 77 billion yen. Using input–output analysis, we estimated the indirect damage costs caused by the repercussions of halting production. Indirect damages across all sectors totaled 91 billion yen. The wholesale and retail trade sector had the largest direct damage costs, while the transportation equipment manufacturing sector has the largest indirect damage costs. © 2013 Wiley Periodicals, Inc. Electr Eng Jpn, 185(4): 25–32, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22306